IDENTIFIKASI SALMONELLA PADA JAJANAN YANG DIJUAL DI KANTIN DAN LUAR KANTIN SEKOLAH DASAR - Mega Mirawati; Estu Lestari; Husjain Djajaningrat (Poltekkes Kemenkes Jakarta III, 2014)
Child street food has become part of everyday children, especially elementary school. Snack food purchased in a less assured of cleanliness can lead to diseases of the gastrointestinal tract due to bacterial contamination . One of the bacteria that contaminate food are Salmonella. According to ISO 2011, the maximum contaminant limit of Salmonella in foods is negatip/25g. This study aimed to identify the presence of Salmonella contamination on foods sold in the elementary school at Pondok Gede. This research is descriptive . Samples of food and drinks sold in elementary school of Pondok Gede . The study was conducted at the Laboratory of Bacteriology of Analis Kesehatan Poltekkes Kemenkes Jakarta III in October-November 2013. The method use in this research was culture . The study of 28 samples of food found 10 samples ( 35.7 % ) contaminated with salmonella. A total of 4 samples ( 26.7 % ) came from the canteen and 6 samples ( 46 % ) from outside the canteen. The results indicate identification of 4 samples (40 %) contaminated with Salmonella typhi and 6 samples ( 60 % ) contaminated with Salmonella paratyphi A. Presence of Salmonella can be caused due to the influence of raw materials , water , presentation , container and environmentalhygiene.Conclusion that street food is found contaminated with Salmonella typhi and Salmonella paratyphi A.